1998
DOI: 10.1093/ajcn/68.3.734
|View full text |Cite
|
Sign up to set email alerts
|

Relation of anthropometry to malaria morbidity and immunity in Papua New Guinean children

Abstract: The interaction between malnutrition and malaria is complex and there is evidence that malnutrition decreases the susceptibility to malaria. To investigate the relation between anthropometric measurements and subsequent malaria morbidity and to examine whether the effect observed was due to interaction with host immunity, we followed for 1 y a cohort of 136 children aged 10 to < 120 mo in Wosera, East Sepik Province, Papua New Guinea. At baseline, 21% were stunted, 10% were wasted, and 5% were both stunted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
2
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 41 publications
4
90
2
10
Order By: Relevance
“…In this study, malaria outcome does not relate to low height for age z-scores, an indicator of achieved height and long term nutritional status. These findings concur with longitudinal study findings where it found that stunted children had a lower incidence of clinical malaria episodes than not stunted children (Genton et al, 1999). This findings contradict a longitudinal study in Gambia where stunting at the start of transmission season was associated with increased incidence of malaria (Deen et al, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, malaria outcome does not relate to low height for age z-scores, an indicator of achieved height and long term nutritional status. These findings concur with longitudinal study findings where it found that stunted children had a lower incidence of clinical malaria episodes than not stunted children (Genton et al, 1999). This findings contradict a longitudinal study in Gambia where stunting at the start of transmission season was associated with increased incidence of malaria (Deen et al, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…Lors d'une étude plus récente menée en Papouasie Nouvelle-Guinée, un retard de croissance staturo-pondéral a paru diminuer le risque de paludisme à P . falciparum [43] . Ces études ont donc suggéré qu'une sous-nutrition, particulièrement une malnutrition protéino-énergétique, aidait à protéger contre le paludisme.…”
Section: Malnutrition Protéino-énergétique Et Paludismeunclassified
“…Malnutrition is the premier causes of stunted growth and increasing mortality and morbidity rates [4][5][6][7]. About 4 of each 5 malnourished children in South-East-Asian (SEA) regions contributing about 83% of their deaths due to mild to moderate malnutrition [8][9][10].…”
Section: Introductionmentioning
confidence: 99%